Arterial hypertension and comorbidity prevalence in climacteric women - N. V. Izmozherova; A. A. Popov; A. N. Andreev; N. V. Tagiltseva; E. V. Kozulina; E. I. Gavrilova (Кардиоваскулярная терапия и профилактика)
Aim. To assess the prevalence of arterial hypertension (AH) and comorbidity in women with climacteric syndrome (CS).Material and methods. This cross-sectional study included 806 female Yekaterinburg citizens (median age 52 years). The prevalence of AH, coronary heart disease (CHD), chronic heart failure (CHF), history of stroke or myocardial infarction, as well as prevalence of pulmonary and gastro-intestinal pathology, osteoarthrosis, carbohydrate metabolism disturbances, and CS was investigated.Results. AH was identified in 68% of the participants, including Stage I, II, and III AH in 30,3%, 26,1%, and 43,6%, respectively. AH was associated with increased rates of CHF, CHD, and long-term disability. In AH patients, clinical symptoms of chronic cholecystitis, carbohydrate metabolism disturbances, abdominal obesity (АО), and knee osteoarthrosis were more prevalent. There were no differences in the prevalence of acid-dependent gastric pathology, obstructive pulmonary disease, and depression. Severe CS was significantly more prevalent in AH patients.Conclusion. In CS women, AH was highly prevalent, especially Stage III AH. AH was associated with increased rates of CHF, CHD, and long-term disability. High rates of АО, carbohydrate metabolism disorders, and osteoarthrosis could negatively affect AH and CHF treatment effectiveness.